2017
DOI: 10.5301/hipint.5000462
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Core Decompression for Treatment of Canine Femoral Head Osteonecrosis Induced by Arterial Ischaemia and Venous Congestion

Abstract: CD displayed greater treatment efficacy for femoral head osteonecrosis caused by VC, but poor efficacy for femoral head osteonecrosis caused by AI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Core decompression may be helpful to alleviate symptoms after surgery (32). A meta-analysis was employed to identify 22 studies using a single surgical core decompression technique (33).…”
Section: Discussionmentioning
confidence: 99%
“…Core decompression may be helpful to alleviate symptoms after surgery (32). A meta-analysis was employed to identify 22 studies using a single surgical core decompression technique (33).…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic necrosis of the femoral head (ischemic necrosis of the femoral head, INFH) is a common disease in clinical practice, and it usually occurs in young adults; lesion occurs at the lesion site, which may be accumulated at the whole hip joint, finally resulting in function loss of hip joint and seriously affecting the patients’ health and life quality (Liu et al, 2017, Zhu and Zhu, 2012). The pathogenesis inducing INFH is complex, blood supply insufficiency of femoral head is a key factor resulting in INFH, it is reported according to many reports that hyperlipidemia is closely related to INFN (Zhang et al, 2012), while leptin plays an important role in many linkages of human metabolic process (Liu et al, 2012); as a kind of endogenous bioactive polypeptide of adipose tissue secretion, adiponectin is able to reflect human lipid metabolism level to a certain degree (Huang, 2015); it is also reported that the level of NO, TNF-α and other correlation factors of INHF patients has relevance with the bone marrow edema of INFH and pain degree (Lin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%